2019
DOI: 10.1029/2018jc014094
|View full text |Cite
|
Sign up to set email alerts
|

Floe Size Effect on Gravity Wave Propagation Through Ice Covers

Abstract: When modeling gravity wave propagation through an array of discrete ice floes, considered as a homogenous elastic continuum, the equivalent elasticity is less than the intrinsic material elasticity of ice. The array behaves increasingly like a collection of rigid floating masses when the floe sizes decrease. Extending a former wave flume experiment with polyethylene plates (Sakai & Hanai, 2002, https://web2.clarkson.edu/projects/iahrice/IAHR%202002/Volume%202/189.pdf), we conducted an experiment with saline ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 36 publications
3
26
0
Order By: Relevance
“…The second, more important reason was consistency between the dispersion relation used and the assumptions underlying the DEM (individual ice floes and elastic interactions between them). It is also worth pointing out that our observations from the laboratory, described in Part 2, as well as the previous analysis of the LS-WICE data by Cheng et al (2018), provide arguments that viscous damping within the floating ice cover in those experiments was not significant and that Eq. (6) represents the laboratory conditions well (notably, the ice floes floated in clear water, as opposed to many observations of wave damping in the MIZ, where the presence of a frazilpancake mixture gives the surface ocean layer high effective viscosity).…”
Section: Definitions and Assumptionssupporting
confidence: 72%
See 2 more Smart Citations
“…The second, more important reason was consistency between the dispersion relation used and the assumptions underlying the DEM (individual ice floes and elastic interactions between them). It is also worth pointing out that our observations from the laboratory, described in Part 2, as well as the previous analysis of the LS-WICE data by Cheng et al (2018), provide arguments that viscous damping within the floating ice cover in those experiments was not significant and that Eq. (6) represents the laboratory conditions well (notably, the ice floes floated in clear water, as opposed to many observations of wave damping in the MIZ, where the presence of a frazilpancake mixture gives the surface ocean layer high effective viscosity).…”
Section: Definitions and Assumptionssupporting
confidence: 72%
“…(25), with α(ω) strongly dependent on the assumed dispersion relation. This result is particularly interesting in view of the results of Cheng et al (2018), who showed that the dispersion relation is strongly affected by floe size, with the wavenumber k increasing with decreasing floe length. The DEM results are presented in Sect.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Initial results of the tests relevant to this study (series 2000 and 3000, as described below) are described in Cheng et al (2017). Recently, Cheng et al (2018) used the same data in an analysis of the influence of floe size on wave dispersion. Other LS-WICE results were used to study floe-size distributions in sea ice broken by waves (Herman et al, 2017(Herman et al, , 2018 as well as wave-induced collisions and floe kinematics (Li and Lubbad, 2018).…”
Section: Experiments Set-upmentioning
confidence: 99%
“…., N f , with N f depending on the floe length L x (see later text). Details related to the preparation of the ice sheets and conduction of the tests can be found in Cheng et al (2018) and will not be repeated here. In this section, we only provide information that is relevant to the present study.…”
Section: Experiments Set-upmentioning
confidence: 99%